GAMBARAN FAKTOR RISIKO JENIS KELAMIN TERHADAP KEJADIAN MALARIA DI SEPAKU PERIODE TAHUN 2021 (Jurnal Medika : Karya Ilmiah Kesehatan, 2026)
Malaria continues to be a significant global health problem, with around 247 million casesand 619,000 related deaths in 2021. In Indonesia, the increase in cases mainly occurred in theeastern region, such as North Penajaman Paser Regency, East Kalimantan. Gender risk factorsare also a concern, with men tending to be more susceptible to the disease. This study used aretrospective descriptive method to describe gender risk factors in malaria sufferers in Sepakuin 2021, finding that 96.1% of sufferers were men. These results support previous findings andcontribute to the understanding of factors that can aid the development of malaria preventionand control strategies.